2017
DOI: 10.1016/j.neuroimage.2017.08.080
|View full text |Cite
|
Sign up to set email alerts
|

BDNF ValMet polymorphism tunes frontolimbic circuitry during affective contextual learning

Abstract: Adaptive learning impairments are common in cognitive and behavioral disorders, but the neurogenetic mechanisms supporting human affective learning are poorly understood. We designed a higher-order contextual learning task in which healthy participants genotyped for the Val66Met polymorphism of the brain derived neurotropic factor gene (BDNF) were required to choose the member of a picture pair most congruent with the emotion in a previously-viewed facial expression video in order to produce an advantageous mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
(86 reference statements)
1
1
0
Order By: Relevance
“…Correspondingly, the atypical genotype group was found to be more severely affected by aphasia as indicated by poorer performance on the WAB-R and the PNT. These results are consistent with studies in healthy individuals (W. Chen et al, 2016;Jabbi et al, 2017;McHughen et al, 2010) and the general stroke population (Kim et al, 2016) where decreased task-related functional brain activation has been reported for individuals carrying the BDNF Met allele polymorphism. Notably, McHughen et al (2010) observed smaller activation volume in a broad sensorimotor network in individuals with the Met allele present in response to right index finger movement.…”
Section: Discussionsupporting
confidence: 92%
“…Correspondingly, the atypical genotype group was found to be more severely affected by aphasia as indicated by poorer performance on the WAB-R and the PNT. These results are consistent with studies in healthy individuals (W. Chen et al, 2016;Jabbi et al, 2017;McHughen et al, 2010) and the general stroke population (Kim et al, 2016) where decreased task-related functional brain activation has been reported for individuals carrying the BDNF Met allele polymorphism. Notably, McHughen et al (2010) observed smaller activation volume in a broad sensorimotor network in individuals with the Met allele present in response to right index finger movement.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the Val homozygous genotype, Met carriers showed a weakened prefrontal response of the ventromedial system to predictive affective signals, dorsolateral prefrontal signaling, which depended on the difficulty of decision-making, and increased prefrontal reactivity of the ventromedial system, which is associated with modulating the decision to avoid failure to complete the task and associated with this loss of money. The data obtained indicate that the Val66Met gene BDNF polymorphism is associated with the functional adjustment of behaviorally significant schemes of the frontolimbic region, especially with the participation of the ventromedial prefrontal cortex, during affective learning of a higher order [5].…”
Section: Genetic Factors Associated With Virtual Navigationmentioning
confidence: 91%